Peran Penyuluh Agama dalam Pelaksanaan Fungsi BP4 bagi Pelestarian Perkawinan - Muthoharoh; Faizah Binti Awad; Nurdin; Sitti Fauziah; Rahmawati (UIN Sunan Gunung Djati Bandung, 2022)
This research is motivated by the increasing divorce rate in Indonesia from 2017 to 2021. This study aims to discuss the role of religious instructors in carrying out the function of BP4 in marriage preservation. This research uses a qualitative approach through literature studies and field studies by applying descriptive-analytical methods. The results and discussion of this study indicate that the role of religious instructors in the sub-district is attached to the function of BP4 as the executor of the marriage preservation program. The conclusion of this study is that religious instructors have tried to carry out their role in the function of BP4, although there are still obstacles that must be faced by extension workers so that the role of extension workers in carrying out the functions of BP4 can be optimal.